Soil microorganisms numbers in the tailing deposition ModADA areas of Freeport Indonesia, Timika, Papua - IRNANDA AIKO FIFI DJUUNA; MARIA MASORA; PRATITA PURADYATMIKA (Biodiversitas Journal of Biological Diversity, 2011)
Djuuna IAF, Masora M, Puradyatmika P (2011) Soil microorganisms numbers in the tailing deposition ModADA areas of Freeport Indonesia, Timika, Papua. Biodiversitas 12: 198-203. The objective of this study was to examine the number and distribution of bacteria, fungi and actinomycetes in the inactive tailing deposition areas of Freeport Indonesia Mining and Gold Company, Timika. One hundred ninety eight composite samples (0-20 cm) were taken from four location of inactive tailing ModADA (Modification Aijkwa Deposition Areas) namely double levee-bottom (fine texture); double levee-middle (medium texture); double levee-top (coarse texture);Mile 21 and transmigration areas of I to V. The conventional method of dilution and Plate Count Agar were used to examine the population of soil bacteria, fungi and actinomycetes. pH and moisture content were also analyzed. The numbers of bacteria in the tailing deposition areas are in the range from 3.48x105 CFU/g soil to 102.83x105 CFU/g soil, soil fungi from 1.51x105 CFU/g soil to 106.61x105 CFU/g soil and actinomycetes range from 0.32x104 CFU/g soil to 113.74x104 CFU/g soil. While in some transmigration areas, the number of soil bacteria, fungi and actinomycetes were lower than in the tailing areas. The number of soil bacteria and fungi were higher than actinomycetes. However, the coefficient of variation of actinomycetes (107%) was higher than soil fungi (89%) andbacteria (68%). Tailing deposition areas are considered as a good habitat for soil microorganisms. Overall, the number of soil organism in the tailings areas are considered medium to high, however to understand their functioning in each location under different land use system, more research are needed to evaluate their roles especially in the decomposition of soil organic matter.